2013
DOI: 10.1186/1477-7525-11-194
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resilience on psychological outcomes in women after preeclampsia: an observational cohort study

Abstract: BackgroundPreeclampsia is a frequent obstetric complication which affects the mother`s and the fetus’s health and can be life threatening. It also has an impact on psychological outcomes. There may be protective variables such as resilience shielding against psychosocial distress in women experiencing these pregnancy complications. The aim of this study was to examine differences in resilience in terms of quality of life, depression and post-traumatic stress symptoms in women after preeclampsia.MethodsFour int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 22 publications
0
31
0
3
Order By: Relevance
“…27 This study endorsed and followed the Consolidated relaxation training and positive emotions. 30,31 Results Table 1 shows the frequency distribution and percentages of demographic characteristics in the intervention and control groups: the two groups were similar in terms of demographic characteristics that may influence maternal anxiety during pregnancy, with no significant differences between the groups.…”
Section: Introductionmentioning
confidence: 99%
“…27 This study endorsed and followed the Consolidated relaxation training and positive emotions. 30,31 Results Table 1 shows the frequency distribution and percentages of demographic characteristics in the intervention and control groups: the two groups were similar in terms of demographic characteristics that may influence maternal anxiety during pregnancy, with no significant differences between the groups.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the German version of the validated 13-item resilience scale (RS-13) was used to measure resilience. [ 14 , 15 ] RS-13 scores range from 13 (low resilience) to 91 (high resilience). Patients with a RS-13 score less than 72 are defined as patients with low resilience and patients with a score of 72 or more have a high resilience.…”
Section: Methodsmentioning
confidence: 99%
“…One clinical study observed that the risk for postpartum depression was associated not to the severity of PE, but rather to its consequences (e.g., perinatal death), even after adjusting for the confounding variables of age, ethnicity, and educational level of the mother (250). While resilience shielding against psychological stress (251) and psychotherapeutic treatment (252) can attenuate the duration of the episode, a previous history of depression coupled with experiencing a preeclamptic index pregnancy can significantly contribute to the onset of PTSD and exacerbate the anxiety of planning future pregnancies (39). The deleterious effects of prenatal maternal psychosocial stressors on fetal development are well documented, where increased incidences of maternal depression (3436) and anxiety (3133) are significantly correlated to low fetal birth weight, IUGR, and premature birth (3236, 38).…”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%